Trends and urban–rural disparities in cervical cancer epidemiology in China, 2005–2018 - Ping Liu; Yuyang Zhu; Haifei Zhou; Runhua Li (Scientific Reports)
Abstract Cervical cancer is a major public health issue in China, characterized by rising incidence and mortality rates over the past years. This study aims to analyze the epidemiological trends of cervical cancer from 2005 to 2018, providing valuable insights for public health policy and intervention strategies. Data were extracted from the publicly available China Cancer Registry Annual Reports (2005–2018), employing joinpoint log-linear regression models to evaluate changes in incidence and mortality rates. The analysis focused on geographic disparities between urban and rural areas, examining how these differences influence overall trends. Incidence and mortality rates were age-standardized using the the Segi’s world population and the fifth Chinese national census of 2000 as references. The incidence of cervical cancer in China increased significantly, rising from 9.10 per 100,000 women in 2005 to 18.10 per 100,000 in 2018, with an average annual percent change (AAPC) of 5.38%. Notably, rural areas exhibited a higher AAPC of 6.28%, compared to 4.54% in urban settings, highlighting the disparities in healthcare access. In 2018, there were 46,626 new cases of cervical cancer in Chinese cancer registry areas, representing 6.63% of all newly diagnosed cancers among women, with 14,737 deaths, making it the seventh leading cause of cancer deaths among females. The age-standardized incidence rate by Segi’s world standard population was 12.00 per 100,000, while the age-standardized mortality rate was 3.49 per 100,000. The incidence was low until age 20, then increased sharply, peaking at 50–54 years, while mortality remained low until age 25 and rose steadily, peaking in the 80–84 age group. Geographic disparities were significant, with the highest incidence and mortality rates found in central and rural regions. The accelerating burden-particularly in rural and Central China-underscores the need to expand organised screening, improve HPV-vaccination uptake, and narrow urban-rural health disparities. Targeted efforts for middle-aged and underserved populations are essential to advance China toward WHO cervical‑cancer‑elimination goals.